How cuckoldry can decrease the opportunity for sexual selection: Data and theory from a genetic parentage analysis of the sand goby, Pomatoschistus minutus - Jones, Adam G. (The National Academy of Sciences, 2001)
Alternative mating strategies are common in nature and are generally thought to increase the intensity of sexual selection. However, cuckoldry can theoretically decrease the opportunity for sexual selection, particularly in highly polygamous species. We address here the influence of sneaking (fertilization thievery) on the opportunity for sexual selection in the sand goby Pomatoschistus minutus, a marine fish species in which males build and defend nests. Our microsatellite-based analysis of the mating system in a natural sand goby population shows high rates of sneaking and multiple mating by males. Sneaker males had fertilized eggs in ≈50% of the assayed nests, and multiple sneakers sometimes fertilized eggs from a single female. Successful males had received eggs from 2 to 6 females per nest (mean = 3.4). We developed a simple mathematical model showing that sneaking in this polygynous sand goby population almost certainly decreases the opportunity for sexual selection, an outcome that contrasts with the usual effects of cuckoldry in socially monogamous animals. These results highlight a more complex and interesting relationship between cuckoldry rates and the intensity of sexual selection than previously assumed in much of the literature on animal mating systems.